Reducción y control de costos en empresa de manufactura con Seis Sigma (Reduction and control of costs in manufacturing company with Six Sigma) - Garza Villegas, Juan Baldemar; Abrego Traslaviña, Ramiro Alfonso (Facultad de Contaduría Pública y Administración, 2015)
Abstract: This case study indicates how the statistics and engineering analysis Six Sigma lead us to find the root-cause operational solutions, resulting on improvement in quality and control of our processes. After defining the real root-cause problem and proving them statistically, it shows us how we can control and improve operations by eliminating waste and generating annual savings in this empirical research, reducing 40% of the use of coatings generating savings greater than $1,000,000.00 MN.